Lymphoma of the scrotum in patients with Down’s syndrome: US appearance. Mini-pictorial essay - Draghi, F. (Elsevier, 2011)
Down’s syndrome is relatively common, and patients who are affected have an increased risk of developing acute leukemia, but not solid tumors. Studies performed in larger patient populations have shown that solid tumors, including lymphomas, are significantly less frequent in Down patients than in children and adults who are not Trisomy 21-affected. Testicular lymphomas are rare and extremely aggressive. Ultrasound (US) combined with color Doppler is essential in the diagnosis and evaluation of treatment results in these lesions. As they are very rare, it was decided to publish this mini-pictorial essay.